Methanol oxidation at single platinum nanoparticles - Chang, X; Batchelor-McAuley, C; Compton, RG (Elsevier, 2021)
The methanol oxidation reaction is studied at the single nanoparticle scale under aqueous alkaline conditions. Upon impacting a potentiostated electrode and after ≤ 1 ms a steady-state reaction limited catalytic current is induced to occur at the platinum nanoparticle (nominal diameter 50 nm); the magnitude of the current is close to that seen for both larger arrays of nanoparticles and polycrystalline ‘bulk’ material suggesting that single entity activity is preserved in ensembles of nanoparticles. This catalytic rate reaches a maximum at a potential of + 0.05 V (vs Ag/AgCl; 3.4 M KCl) with a current density of 0.3 ± 0.2 mA cm−2. However, at very short timescales (<1 ms) the single nanoparticle response reveals the occurrence of an initial rapid charge injection event. This charge injection is consistent with the one-electron oxidation of a monolayer of methanol prior to establishment of the steady-state.